Consumer Behavior and Business Strategy During the Early Stages of the COVID-19 Pandemic - Andhy Setyawan; Fandy Tjiptono; Dadi Adriana (Manajemen dan Bisnis, 2022)
Consumer behavior is dynamic and contextual. An individual’s consumption habit is formed over time and is influenced by many internal and external factors. The consumption habit itself reflects what, where, when, why, and how to choose, purchase, consume, and dispose goods and services. When the COVID-19 pandemic hit, all consumers around the globe were forced to adapt into the never-happened-before realities, such as regional and national lockdowns, stay-at-home campaign, social/physical distancing policy, mandatory quarantine, and self-isolation. Utilizing available and accessible published materials, this paper aims to examine the significant impacts of the outbreak on consumer behavior in Indonesia and identify how the businesses respond to the changes in consumer behavior caused by the coronavirus. The timeframe of the analysis focuses on the early stages of the pandemic. Using the framework developed by Sheth (2020), the present study found supporting evidence of the eight impacts of COVID-19 on consumer behavior (e.g., hoarding behavior, improvisation, and the adoption of digital technology) in Indonesia. Furthermore, companies were found to respond to the pandemic and changes in consumer behavior by employing a combination of four business strategies: survival strategy, synchronizing strategy, stretching strategy, and shifting strategy.